FUNCTIONAL STATE OF THE MASTICATORY MUSCLES OF PATIENTS WITH DEFECTS OF DENTITION, WHICH ARE COMPLICATED BY DENTOALVEOLAR DEFORMITIES - O. V. Bida; Yu. I. Zabuha (Український стоматологічний альманах)
The importance of the research. An increase number of people with dentition defects has been observed during last years. If dentoalveolar deformations are not timely substituted by dentures, they will be complicated by dentoalveolar deformations, violation of occlusal ratio and other pathologies. Temporomandibular joints are involved in the pathological process at untimely replacement of dentition defects. Morphological disorders are accompanied by functional violations of biodynamic balance of masticatory muscles, often in the stage of decompensation.